Chemistry - Chang, Raymond (WCB/McGraw-Hill, 1998)
The book provides a firm foundation in chemical concepts and principles, the three-dimensional atomic and molecular structures that are the basis of chemical activity. It also deals with the role chemistry plays in contemporary life and their curiosity about the "central science"